A thermal energy storage system provided with an adsorption module – Dynamic modeling and viability study. (15th October 2016) - Fernandes, M.S.; Brites, G.J.V.N.; Costa, J.J.; Gaspar, A.R.; Costa, V.A.F.
Highlights: A dynamic model of a heat storage system with an adsorption module is proposed. System designed to increase the storage efficiency of hot water storage systems. Influence of the tanks, condenser and evaporator dimensions is investigated. 6–7% savings in annual backup energy are attained with each individual component. Up to 16% savings in annual backup energy are reached with the overall system. Abstract: The dynamic model of a heat storage adsorption device is presented. The adsorption module operates with the silica-gel/water pair and is capable of storing the thermal energy received from the hot water of the storage tank where it is immersed, to give it back later as adsorption heat. The module is applied to a solar thermal energy system and assessed through a set of parametric tests. It is found that higher condenser lengths and larger pre-heating water tank volumes always improve the system's performance. For a selected fixed heat exchange area, smaller evaporator tube diameters are found to improve the system's performance, while reducing the number of tubes of a settled diameter has a negative effect. It is also found that the system's performance tends to decrease by increasing the main tank's volume, thus requiring even larger adsorbers for larger tanks. Throughout this exploratory study, the adsorption system always presents higher performances when compared with a similar conventional storage system (up to 16% savings in annual backup energy), showing promising perspectives for the overall optimization and application studies, and presenting an attractive solution to increase the thermal storage capacity of solar thermal systems.